Socially just pedagogies and social justice: The intersection of teaching ethics at higher education level and social justice - Klaasen, John (HTS teologiese studies, 2020)
This article is part of a longer term project between the Department of Religion and Theology at the University of the Western Cape and Umea University in Sweden. At both the institutions the teaching of ethics as a module within social science curricula has been an important focus area. The critical investigation of the growth of the ethics modules in the Department of Religion and Theology addresses questions of the growth in the number of students taking ethics as a module that have been escalated in the last few years. This research seeks to explore social justice as a pedagogy to teach ethics. The article investigates the relationship between socially just pedagogies and social justice as a means of knowledge production. The ethics modules and students at the Department of Religion and Theology at the University of the Western Cape are the context of the study, and different socially just pedagogies will be investigated as relevant and significant pedagogies for teaching ethics for social change. Particular attention is given to the interaction between the lecturer, student and non-human phenomena as means of knowledge production. The nature of the interaction determines the effectiveness of pedagogies for a social justice agency.